Precipitation Trends Analysis in Southwest Asia during the Last Half Century - sayyed mohammad hosseini (تحقیقات کاربردی علوم جغرافیایی)
Precipitation is a climatic elements that have temporal - spatial distribution. In this research database of Global Precipitation Climatology Centre (GPCC) with a resolution 0.5×0.5 degree for 50 year is used, that was constituted with dimensions of 12800*600. Temporal data are on the columns and pixels (spatial data) located on the rows. The results show an increasing trend in spring and fall but in summer and winter precipitation trend has been decreased. The most amount of precipitation is located in the northern parts of the Black Sea and Mediterranean Sea, Southeast Asia, southern coast of the Caspian and Central Zagros Mountains. Most of Middle East (about %95) have not trend and only in some parts of Kazakhstan, Afghanistan, Pakistan ,central Iran, and areas in lower-latitude have positive trend and some East and northwest parts of Iran and some parts of Middle East also have decreasing trend of precipitation. The highest percent of area of precipitation trend gradient is 0 to 0.5.